2008
DOI: 10.3852/mycologia.100.2.227
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence analysis of herbarium specimens facilitates the revival of Botrytis mali, a postharvest pathogen of apple

Abstract: The fungus Botrytis cinerea has been widely accepted as the species responsible for causing gray mold decay of apple, although a second species causing apple decay, B. mali, was reported in 1931. Botrytis mali was validly published in 1931, nevertheless it has always been considered a doubtful species. To study the relationship of Botrytis isolates causing gray mold on apple, DNA sequence analysis was employed. Twenty-eight Botrytis isolates consisting of 10 species were sampled, including two B. mali herbariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Phylogenetic analyses of Botrytis species using three nuclear gene sequences of G3PDH encoding glyceraldehyde-3-phosphate dehydrogenase, HSP60 encoding heat-shock protein 60, and RPB2 encoding DNA-dependent RNA polymerase subunit II corroborated the morphological delimitation of Botrytis species by Hennebert (1973) and Yohalem et al (2003). O'Gorman et al (2008) indicated that phylogenetic analysis based on the partial sequences of b-tubulin gene and G3PDH supported the previous work by Ruehle (1931) on the classification of B. mali Ruehle, the causal agent of postharvest decay of apple, as a unique species. Moreover, information on the sequence of NEP2 coding for necrosis and ethylene-inducing protein 2 can be used for designing polymerase chain reaction (PCR) primers to distinguish different species of Botrytis (Mirzaei et al 2008).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Phylogenetic analyses of Botrytis species using three nuclear gene sequences of G3PDH encoding glyceraldehyde-3-phosphate dehydrogenase, HSP60 encoding heat-shock protein 60, and RPB2 encoding DNA-dependent RNA polymerase subunit II corroborated the morphological delimitation of Botrytis species by Hennebert (1973) and Yohalem et al (2003). O'Gorman et al (2008) indicated that phylogenetic analysis based on the partial sequences of b-tubulin gene and G3PDH supported the previous work by Ruehle (1931) on the classification of B. mali Ruehle, the causal agent of postharvest decay of apple, as a unique species. Moreover, information on the sequence of NEP2 coding for necrosis and ethylene-inducing protein 2 can be used for designing polymerase chain reaction (PCR) primers to distinguish different species of Botrytis (Mirzaei et al 2008).…”
Section: Introductionsupporting
confidence: 55%
“…So far, 26 species of Botrytis have been described based on these morphological characteristics (Hennebert 1973;Yohalem et al 2003;Wang et al 1996;O'Gorman et al 2008;Zhang et al 2010). Recently, DNA-based molecular techiniques have been widely used to identify fungi, including Botrytis species.…”
Section: Introductionmentioning
confidence: 97%
“…Though protocols for the extraction of DNA from herbarium material exist (Aras and Cansaran 2006;Cubero et al 1999;Telle and Thines 2008), they still cannot be applied routinely like for living cultures. Current studies successfully retrieving molecular data from fungal herbarium material hitherto worked with epigeous and hypogeous macrofungi (Góes-Neto et al 2005, Brock et al 2009 or dried agar slants with microfungi (O'Gorman et al 2008). In this study, DNA was extracted from microfungal colonies colonizing natural substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of Peronospora blight on opium poppy was also determined to be Peronospora arborescens and not Paraschistura cristata using type specimens from the early 19th century (Montes-Borrego et al, 2008). Support for the name of the postharvest rot of apple as Botrytis mali was shown after conducting molecular phylogenies from DNA extracted from the earliest described diseased apples in herbarium samples (O'Gorman et al, 2008). A realtime PCR diagnostic was developed to distinguish common corn rust, Puccinia sorghi, from southern corn rust, Puccinia polysora.…”
Section: Taxonomic Disputesmentioning
confidence: 99%